DENTAL ANXIETY AMONG PATIENTS UNDERGOING EXTRACTION OF TEETH - Gulsanga Shams; Bushra Mehboob; Abida Anwar; Laiba Jalal; Raheela Wajid; Hamayal Waseem Khattak (Pakistan Oral & Dental Journal, 2024)
People avoid going to the dentist due to fear and anxiety related to dental procedures. The study aimed to determine the estimated percentage of anxiety among individuals undergoing exodontia and the association between gender, previous dental experience, and dental anxiety. A descriptive cross-sectional study was conducted in the oral and maxillofacial surgery ward of Peshawar Dental College Hospital from March to May 2022. A non-probability consecutive sampling technique was used. All adult patients were taken in the survey. Medically compromised patients were not included in the study. The Modified Dental Anxiety Scale was used to assess the anxiety of dental patients. The Chisquare test was used to find an association between variables. Out of 120 respondents, 57(47.5%) were male and 63(52.5%) were female. Most of the respondents were in the age group of 18-29 (40%). The majority (42.5%) of patients had a past dental history of extractions and had rated previous dental experience on a scale of 1-3 (58.5%). MDAS score 1-5 (31.7%) and 6-10 (25%) was found frequently. 16.7% of patients reported experiencing high levels of dental anxiety. A significant Association of MDAS was found with gender p=.001 and previous dental experience p=.041. Gender and previous dental experience impact the anxiety levels of patients undergoing teeth extraction.